History of Computer Networks - Hasanuddin Sirait (Yayasan Adra Karima Hubbi, 2024)
With has each other connected so between computer can interact And send data. Data transmission is carried out To use spread information And data processing becomes something information . So that man as user information can take advantage of it in necessary jobs? speed And data accuracy and accuracy information. Various network models computer seen of type and benefits network the such as one to one, one to anywhere , many to one and many to many. Development system network computer This started since 1960s by? company electronics famous like ARPANET. Development network computer the will explained on discussion following .